2012
DOI: 10.1177/1012690212469189
|View full text |Cite
|
Sign up to set email alerts
|

Make me proud! Singapore 2010 Youth Olympic Games and its effect on national pride of young Singaporeans

Abstract: Politicians and sports organizations have often relied on economic benefits to justify their decisions in hosting major sports events in their countries. Consequently, there are comparatively few studies on the non-economic benefits of hosting major sports events. The purpose of this research is to determine whether there is any change in the level of national pride in the hosting of the Youth Olympics Games held recently in Singapore in 2010. Two separate surveys were conducted among students from a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…To our best knowledge, special attention to the local youth was paid solely by Leng, Kuo, Baysa-Pee, and Tay (2014) and Götzel (2013). Using the YOG in Singapore in 2010, Leng et al (2014) focused on the change in national pride on the part of the local youth community by surveying Singaporeans two months prior to and three months after the YOG 2010. Götzel (2013) analysed the perception of the Culture and Education Programme among school pupils participating in an initiative called "World Mile Project" (WMP) on the occasion of the YOG 2012 in Innsbruck.…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, special attention to the local youth was paid solely by Leng, Kuo, Baysa-Pee, and Tay (2014) and Götzel (2013). Using the YOG in Singapore in 2010, Leng et al (2014) focused on the change in national pride on the part of the local youth community by surveying Singaporeans two months prior to and three months after the YOG 2010. Götzel (2013) analysed the perception of the Culture and Education Programme among school pupils participating in an initiative called "World Mile Project" (WMP) on the occasion of the YOG 2012 in Innsbruck.…”
Section: Introductionmentioning
confidence: 99%
“…Among male consumers, social influence is also more likely to have a larger effect through informational influence. Earlier studies have indicated that males are more likely to be highly involved in sports (Leng et al 2014, Denham 2010, Scheerder et al 2011. As such, similar to the above arguments, male consumers are more likely to be concerned on the enhancement of sport performance by the sports product and are thus more likely to seek information on the brands and products.…”
Section: Discussionmentioning
confidence: 59%
“…Earlier studies have found that sport involvement can affect sports consumption behaviour (Chew & Leng, 2014). In addition, given the gendered nature of sport, the level of sport involvement is generally higher among males (Leng, Kuo, Baysa-Pee, & Tay, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%